Perfectly creamy frozen yogurt : 56 amazing flavors plus recipes for pies, cakes & other frozen desserts - Weston, Nicole (Storey Publishing, 2018)
Learn to make frozen yogurt at home thats just as light, smooth, and delightful as what you buy. You'll use Greek yogurt as a base and a basic ice cream machine to make these 56 flavor recipes that range from traditional to artisanal, including black cherry vanilla, toasted coconut, peach Melba, chai spice, watermelon, maple bacon, chocolate malted, pistachio, and browned butter pecan. An additional 50 recipes for treats like blueberry sugar cookie sandwiches, brownie baked Alaska, Neapolitan semifreddo, cinnamon bun pops, and salted caramel swirl bonbons ensure this is the sweetest guide ever to making and enjoying frozen yogurt.